My wonderful Christmas tree - Ipcar, Dahlov Zorach, 1917- (Yarmouth, Me. : Islandport Press, 2008)
Looking out her window on Christmas Eve, the author introduces the numbers from one to twelve as she spies several animals nestled in the boughs of an evergreen tree.
Originally published: Gannett Books, 1986.
Maine author and illustrator. Dahlov Ipcar lives near Bath, Me.
Keywords: Animals -- Juvenile fiction; Counting; Christmas stories; Stories in rhyme